Recognition of Older Adults as a Heterogeneous Social Group - Sanja Ivic; Goran Nikolic; Milan Igrutinovic (Trans/Form/Ação)
Human rights of older adults are still not sufficiently developed. This paper will explore how the rights of older adults are regulated by European law and whether European law sufficiently recognizes older adults as a heterogeneous social group.  The population of the European Union is growing older. According to the European Commission’s reports, age discrimination in Europe is widespread. Therefore, the concept of work and retirement system as well as the perception of older adults should be transformed. Discrimination against older adults and various forms of inequality are amplified by the COVID-19 pandemic.